The Relationship Between Mother's Trust In Baby Massage Performed by A Shaman With The Giving of Complementary Therapy - Wijayanti, Heny Noor; Novika, Almira Gitta; Lestari, Adinda Cahaya (Universitas Andalas, 2024)
Research Background : The habit of baby massage in Indonesian society is something that has been known for a long time, but unfortunately, in this case the shaman is an important role. A shaman is considered a person with charismatic powers who has a special authority that is self-acquired and is a gift from God. Giving baby massage to a shaman has become a tradition that has been passed down from generation to generation. Baby massage is one of the oldest traditional cultures in Indonesia and even in the world. Research Objective: To determine the relationship between mother's trust in baby massage carried out by a shaman with the giving of complementary therapy. Research Methods: The type of research used is analytical research with a cross-sectional design. The research location was carried out in the working areas of 4 Kendal Regency Public Health Centers and 3 Sleman Regency Public Health Centers. The research was carried out in July-September 2023. The population used in the research was all mothers with babies. The sample for this research was mothers who had babies aged 0-24 months who were selected for research based on the results of sampling with a total sample of 118 people taken by purposive sampling. The data analysis used is univariate and bivariate analysis. The results of the study: The results of statistical test there is a relationship between the mother's trust in baby massage by a shaman with the giving of complementary therapy (p = 0.009). Conclusion: From the results of this research, it is hoped that the work area will receive results Public Health Centers to open baby massage classes for mothers so that mothers are motivated to do baby massage alone.